The therapeutic effect of glucocorticoids on type II respiratory failure, heart failure, and massive pericardial effusion caused by hypothyroidism: A case report - Wang, Jingyue; Li, Xiangjun; Shen, Botao; Wang, Shipeng; He, Jiahuan; Wang, Yushi (Frontiers in Pharmacology, 2022)
Background: Hypothyroidism is a disease commonly seen in outpatient clinics, but occasionally, it can cause severe cardiovascular and respiratory diseases, requiring hospitalization. The patient reported here failed to wean from invasive ventilation multiple times after routine treatment and was finally successfully weaned on the fifth day of high-dose methylprednisolone intravenous drip and euthyrox oral administration, highlighting the application value of steroids for patients with respiratory failure caused by severe hypothyroidism. Case report: This paper reports the early application of glucocorticoids for successful treatment of a patient with type II respiratory failure, heart failure, and massive pericardial effusion caused by hypothyroidism. Conclusion: This case report suggests that hypothyroidism may be a cause of type II respiratory failure and that a combination of euthyrox and corticosteroids can effectively treat the disease. Clinical workers should consider the role of thyroid function in diagnosis, and the admission team should include it in the monitoring scope. Moreover, the role of hormones in the treatment of patients with severe hypothyroidism should not be ignored, and timely treatment is necessary.